Motivating municipal engineering students to learn computer language with integration of specialised design problems and programming - Zhang, Hui; Zhang, Haihan; Zhang, Qian (Innovations in education and teaching international, 2024)
Computer programming and municipal engineering (ME) students' specialised knowledge are still poorly integrated, leading to limited improvement of students' programming abilities. This paper describes an effective attempt in ME at Xi'an University of Architecture and Technology (XAUAT). Students were divided into several teams and required to develop software tools for ME design problems using Visual C++ 6.0. In this teaching approach, students need to identify the solutions by integrating knowledge in mathematics, physics, chemistry, basic engineering science, and ME. Moreover, students should develop programmes with friendly interfaces, essential prompts, and reliable results. The example programmes, positive feedback from the survey, and better performance in the final examination proved that the students' abilities of knowledge application and problem-solving had been developed, and their motivation in learning programming had been improved.